A Literature Review of Women's Sports in Social Dynamics: Foucault's Genealogy - Desviyanti, Elsya; Vai, Aref; Rahmatullah, Muhammad Imam (Journal of Physical Education Health and Sport, 2023)
This review article provides an overview of the reality of sports women in the life of social dynamics. The method used is a literature study or literature review. Literature study or literature review is a research design used to collect data or sources related to a particular topic by reading, recording and managing research materials. The purpose of this method is to reveal various theories that are relevant to the problem under study. In the search conducted through the keyword "sportswomen" on several websites, 40 findings relevant to the research were displayed. Then it was re-executed according to the needs of the researcher so that 6 article data were obtained. The results showed that women in the world of sports experienced a very rapid development. Many achievements obtained by female athletes from the 1900 Paris Olympics to the 2020 Olympics in Tokyo show the increasing contribution of female athletes. In addition to the acquisition of achievements, women occupy sports organizations as women leaders in sports. The existence of women in the world of sports shows that this masculine world does not only look at gender but everyone has the right to be involved in it.